Elementos para o estudo da ocupação romana na foz do Mondego. - Penajoia, Marco (2021)
In order to improve the knowledge inherent to the Roman occupation of the Figueira da Foz territory, is presented a brief review of some ceramic fragments deposited in the Santos Rocha Municipal Museum. Materials identified by Santos Rocha, as well as others, from more recent archaeological prospecting, are brought up to discussion. These materials come from geostrategic sites, and part of them are in a framework of seariver dynamics, which fits the maritime interface with the Mondego/Pranto river and its former associated watercourses. In this context we draw attention to the findings of the ovens of Pedrulha (Brenha) and Vale do Gonçalo (Alhadas), Monte da Amoreira (Maiorca) and the Igreja Velha do Negrote (Alqueidão), in the south of Figueira da Foz territory. Keywords: Mouth of Mondego; Santos Rocha Museum; Roman Occupation; Ovens; Mortarium; Dramont D2.